Induksi Mutasi Curcuma zedoaria (Christm) Roscoe dengan Irradiasi Sinar Gamma - Poerba, Yuyu Suryasari; Martanti, Diah (Universitas Atma Jaya Yogyakarta, 2009)
Curcuma zedoaria (Zingiberaceae) is one of Curcuma spp. used as stomachic,carminative, haematic and styptic medicines. Dried rhizomes of C. zedoaria containessential oil and curcuminoids. Induced mutation of this species would provide andhelp plant breeders to improve and select better quality of the plant. The presentstudy was carried out to determine LD-50% of gamma irradiation of C. zedoaria, toinduce genetic variation using gamma irradiation, and to assess genetic diversityamong mutant genotypes using random amplified polymorphic DNA (RAPD)markers. The LD-50% of gamma irradiation was achieved at 813.32 rad. Chlorophyllmutations were recorded at vM1 and vM2. Result of genetic analysis showed thatRAPD profiles were different from that of the control, and genetic dissimilaritiesamong mutant genotypes were higher than that of the control.